2020
DOI: 10.1049/ccs.2019.0021
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of muscle synergy structure while walking under increased postural constraints

Abstract: It is hypothesised that specific groups of muscles aka muscle synergies (MSs) are combined by the central nervous system to control a wide repertoire of movements and also simplify motor control. Therefore, studying MSs during human locomotion is of significance, as it may reveal neuromuscular strategies for postural stability. In this study, the authors aimed to use the hypothesis of MSs to identify specific muscle co-activations during overground walking and slacklining where postural perturbations were gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…44 Moreover, slackline as a sport may assist individuals in developing postural response that requires stability in a similar challenging situation. 1 A higher knee flexion kinematic responses to lower the Center of Mass (COM) is one such behavior that was observed previously to provide knee stability in forward motion. 1 The results from our study showed changes in the dimensionality of MS for three different groups on a novel task.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…44 Moreover, slackline as a sport may assist individuals in developing postural response that requires stability in a similar challenging situation. 1 A higher knee flexion kinematic responses to lower the Center of Mass (COM) is one such behavior that was observed previously to provide knee stability in forward motion. 1 The results from our study showed changes in the dimensionality of MS for three different groups on a novel task.…”
Section: Discussionmentioning
confidence: 78%
“…1 A higher knee flexion kinematic responses to lower the Center of Mass (COM) is one such behavior that was observed previously to provide knee stability in forward motion. 1 The results from our study showed changes in the dimensionality of MS for three different groups on a novel task. Therefore, training on a slakcline may improve the postural stability among individuals affected with ML instability by incorporating new synergies.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations